Investigation of power factor on harmonic effect due to types of voltage source - Risnidar Chan Bahaudin, Ir.; Ismail, Daut, Prof. Dr.; Syafruddin, Hassan; M. I., Yussof; Rosnazri, Ali; Dina Maizana, Maiz Ahmad; Indra, Nisja; Masykur (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.